The gut–brain connection: microbes’ influence on mental health and psychological disorders - Ataei, Pegah; Kalantari, Hamidreza; Bodnar, Tamara S.; Turner, Raymond J. (Frontiers in Microbiomes, 2026)
The human gut microbiome has emerged as a pivotal modulator of brain function and mental health, acting through intricate bidirectional communication along the gut–brain axis. Mounting evidence suggests that microbial communities influence neurodevelopment, neurotransmission, and behavior via pathways involving the vagus nerve, immune signaling, and microbiota-derived metabolites such as short-chain fatty acids and neurotransmitter precursors. This review critically examines the mechanistic underpinnings of microbiota–brain communication and evaluates current findings linking dysbiosis to psychiatric conditions, including depression, anxiety, schizophrenia, autism spectrum disorder, and bipolar disorder. In addition, it assesses the therapeutic potential of microbiome-targeted interventions—such as probiotics, fecal microbiota transplantation (FMT), and precision dietary modulation—in ameliorating neuropsychiatric symptoms. While the field holds considerable promise, limitations, including correlational study designs, small sample sizes, and a lack of standardized methodologies, underscore the need for rigorous, large-scale clinical trials. A deeper understanding of host–microbe interactions may catalyze a paradigm shift in psychiatric treatment, paving the way for novel, personalized microbiome-based therapeutics.